Stevens-Johnson Syndrome (SJS)-Toxic Epidermal Necrolysis (TEN) overlap in a 61-year old woman: a case report - Luh Gede Melia Puspita Sari; Tjok Dalem Pemayun (Intisari Sains Medis, 2020)
Background: Epidermal necrolysis (EN) is a rare life-threatening reaction. The exact cause of this disease is unknown. However, the drug is one of the main factors as a cause. EN differentiated based on the extent of skin detachment limited to less than 10% of the body surface area (BSA) in SJS, 10%-30% BSA in SJS/TEN overlap, and greater than 30% of the BSA in TEN. SJS and TEN can occur at various ages, but more often occur at the age of 40 years. Mortality was almost 30% in SJS/TEN overlap patients. Management for SJS and TEN is the cessation of drugs that are thought to be the cause and other supportive therapies.Case presentation: A 61-year-old female with SJS-TEN overlap, who presented epidermal detachment, is about 10-30% with a positive Nikolsky sign. She had a history of taking medication, such as paracetamol, amoxicillin, and buscopan, before lesion appeared. There were multiple lesions widespread, macula hyperpigmentation multiple, erosion from the bullae that has broken, there also erosion covered by black crust, and various erosions covered with black, brown crusts on lip mucosa and also secret on both eyes. The management of this patient was a cessation of suspected drug and supportive therapy. The patient’s condition was improved within a few weeks, and no sequelae found.Conclusion: SJS-TEN overlap is one of the epidermal necrolysis in which skin detachment 10-30% BSA. The management was a cessation of all suspected drugs, administering high doses of steroids and other supportive therapies.